PENGARUH AKUNTANSI FORENSIK DAN AUDIT INVESTIGASI TERHADAP PENGUNGKAPAN FRAUD PELAPORAN KEUANGAN (Studi Empiris pada Kantor Akuntan Publik (KAP) Daerah Jakarta Selatan) - Mulia Rahmah; Ekarista Isowati Sinaga (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
The effect of forensic accounting on fraud disclosure in local public accounting firms South Jakarta, The effect of investigative audit on fraud disclosure in local public accounting firms South Jakarta, The effect of forensic accounting and investigative audit on fraud disclosure in local public accounting firms South Jakarta. The research method used is a quantitative research method. This study has a population of 150 auditors who work at a public accounting firm in South Jakarta. The total data used is 70 auditors. Forensic accounting has a positive effect on fraud disclosure, The investigative audit has a positive effect on fraud disclosure, Forensic accounting and investigative audits have a positive effect on fraud disclosure